Digital Tools across the Genre-Based Approach Cycle: Enhancing EFL Learning through Technology Integration - Intan Aprilia, Novi; Noor Farida, Alief (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This research study presents descriptive qualitative with a conceptual framework for utilizing digital tools ,including Padlet, Jamboard, blogs, AI-generated texts, Google Docs, Grammarly, and Write & Improve. in the EFL writing class through the GBA cycle. In the digital era, integrating technology into GBA processes promotes the development of language learning more efficiently. The theory used in this research consists of socio-constructivism theory, connectivism theory, and self-regulated learning to link digital tools with Ganre-Based Approach stages in EFL, such as Building Knowledge of the Field, Modeling of Text, Joint Construction of Text, and Independent Construction of Text. This present integration highlights the potential of digital tools, including Padlet, Jamboard, Textual Clustering Blog, AI-generated texts, Google Docs, The Object’s Writing Games, Grammarly, and Write & Improve, to enhance peer collaboration, guided support, and independent learning throughout the writing process. The results demonstrate a significant connection between GBA stages and the pedagogical benefits of these tools, which contribute to enhancing students ' writing performance and motivation. Therefore, the research offers both theoretical and practical contributions by providing a technology-oriented model that facilitates the effective use of GBA EFL.